Storage Stability of Latex Modified Bitumen - Azahar, Nurain Izzaty (IRC, 2019)
The use of latex modified bitumen can increase the performance of pavement work. Polymer modified bitumen are usually prepared at high temperatures and subsequently stored for a period time, also some high temperatures. A coupled phase-field model of diffusion and flow is developed to stimulate and predict the polymer modified bitumen storage stability and phase separation. An unstable polymer modified bitumen starts to separate into phases by diffusion because of poor polymer-bitumen composition. The attention of this paper is focused on the analysis of optimum composition of materials that cause least separation of latex and bitumen. Materials that involved in latex modified bitumen are bitumen with grade of 60/70 with latex that obtained from Lembaga Getah Malaysia. In order to determine the optimum percentage of latex composition in latex modified bitumen, author use three different percentage of latex, 3% and 6% from the weight blend of base bitumen. The outcome of this study may thus assist in future efforts of ensuring storage stability and sustainable application of latex modified bitumen.